Arahan Pengembangan Kawasan Pariwisata Terpadu di Pulau Kei Kecil, Kabupaten Maluku Tenggara - Cici Rahmayanti; Marly Valenti Patandianan; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2022)
Southeast Maluku Regency has a very beautiful and interesting beach tourism with a close distance from each other. These tourist objects is still develop by the local and managed by the local community. This study aims to integrate the three coastal tourism locations in Southeast Maluku Regency, namely Ngurbloat Beach, Ngursarnadan Beach, and Ohoidertawun Beach which are included in Tourism Strategic Area (TSA) Maritime Urban Eco-tourism. The method used in this research is descriptive analysis qualitative, spatial, delphi, triangulation, and SWOT. Based on the results of the study, there were 14 internal factors and 8 external factors that influenced the development of an integrated tourism area on Kei Kecil Island. Based on these factors, a direction and consept for tourism development is made by using a triangulation and SWOT analysist (strength-oppertunities/S-O strategy) which is divided into the core zone (Ngurbloat Beach), support zone (Ngursarnadan Beach), and the outer zone (Ohoidertawun Beach).